2004
DOI: 10.1203/01.pdr.0000100477.59081.fe
|View full text |Cite
|
Sign up to set email alerts
|

Development of Acute Edema Following Cerebral Hypoxia-Ischemia in Neonatal Compared with Juvenile Rats Using Magnetic Resonance Imaging

Abstract: We hypothesized that the evolution of cerebral edema accompanying cerebral hypoxia-ischemia is dependent on age and that such differences would be detectable using magnetic resonance imaging methods. Thus we examined in immature and juvenile rats the relationship between hypoxic-ischemic changes in T 1 and T 2 and the alterations in brain water content, as assessed by differences in tissue wet-dry weights. One-and 4-wk-old rats were anesthetized and subjected to unilateral carotid artery occlusion and subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…As such, use of the method has primarily been limited to lower field strengths, generally 1.5T and below, where patient-specific B1 variations are small. While DESPOT1 has been successfully applied at higher fields, such as at 9.4T (19), the FOV utilized in these applications have been small enough to justify the assumption of a spatially uniform B1 field. High field (3T and above) large-volume (ie, whole-brain) T1 mapping with DESPOT1, however, has remained challenging.…”
Section: Discussionmentioning
confidence: 99%
“…As such, use of the method has primarily been limited to lower field strengths, generally 1.5T and below, where patient-specific B1 variations are small. While DESPOT1 has been successfully applied at higher fields, such as at 9.4T (19), the FOV utilized in these applications have been small enough to justify the assumption of a spatially uniform B1 field. High field (3T and above) large-volume (ie, whole-brain) T1 mapping with DESPOT1, however, has remained challenging.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Although severe injury is characterized by tissue loss and necrosis in both white matter (WM) and gray matter (GM), 3 mild injury leads predominantly to WM damage. 4 Such selective WM damage in mild hypoxia-ischemia may be due to apoptosis of immature oligodendrocyte progenitors and dysfunction of mature oligodendrocytes, which are susceptible to HI injury.…”
mentioning
confidence: 99%
“…1 In mild neonatal HI, WM injury is diffuse and noncystic, whereas in severe neonatal HI focal cystic lesions in the WM often ensue. By varying the duration of hypoxia in the well established model of neonatal HI using a D7 rat, the severity of brain injury may be modified [2][3][4] leading to selective WM injury with relative sparing of gray matter (GM) 2 in the mild HI model and global necrosis and infarction in both WM and GM in the severe HI model. 4 The histological findings in the WM of mild HI injury include gliosis and reduced myelination, 5 and in severe HI injury, there is neuronal necrosis and infarction.…”
mentioning
confidence: 99%
“…Previous animal studies 2,3,5,9,10 have demonstrated that conventional MRI sequences such as T1-weighted imaging (T1WI) and T2-weighted imaging (T2WI), and diffusion-weighted imaging (DWI) measuring trace, could detect HI-induced brain damage. Diffusion tensor MR imaging (DTI) allows the measurement of the directional diffusivities of water and is more sensitive than conventional MRI sequences in detecting WM 1 injury.…”
mentioning
confidence: 99%